Overview of the research of representing the family and spare time on Facebook and Instagram - Golubović, Marija (Sociološki pregled, 2021)
The process of displaying family in the era of social networks has acquired a new dimension, as presented to us by Charlene S. Shannon-McCallum, who was exploring the display of family on Facebook and Instagram. Based on a theoretical review and the research results, the author points out the influence and significance that posting family photos on social networks has on family life.